The Biblical Qumran Scrolls : transcriptions and textual variants - Ulrich, Eugene Charles, 1938-; Cross, Frank Moore.; Baillet, Maurice. (Vetus Testamentum, Supplements, 2010)
The Biblical Qumran Scrolls presents all the Hebrew biblical manuscripts recovered from the eleven caves at Qumran. It provides a transcription of each identifiable fragment in consecutive biblical order together with the textual variants it contains. These manuscripts antedate by a millennium the previously available Hebrew manuscripts. They are the oldest, the best, and the most authentic witnesses to the texts of the Scriptures as they circulated in Jerusalem and surrounding regions at the time of the birth of Christianity and Rabbinic Judaism. The purpose is to collect in a single volume all the biblical editions originally published in a wide variety of books and articles.